Vorwort: (Un)Eingeschränkt entscheiden. Reproduktionspolitiken und Selbstbestimmung. - Eremin, Oxana; Langer, Antje; Mattei, Annalisa; Mahs (Hrsg.), Claudia (GENDER. Zeitschrift für Geschlecht, Kultur und Gesellschaft. Schwerpunkt: Reproduktionspolitiken und Selbstbestimmung)

Rezension zu: Corinna Schmechel (2022). Auspowern und Empowern? Eine Ethnohraphie queerer Fitnesskultur. Bielefeld. - Eremin, Oxana (GENDER. Zeitschrift für Geschlecht, Kultur und Gesellschaft)

A Mixed-Methods Study on User Experiences and Challenges of Recovery Codes for an End-to-End Encrypted Service - Höltervennhoff, Sandra; Wöhler, Noah; Möhle, Arne; Oltrogge, Marten; Acar, Yasemin; Wiese, Oliver; Fahl, Sascha (33rd USENIX Security Symposium, USENIX Security 2024, Philadelphia, PA, USA, August 14-16, 2024)

The Challenges of Bringing Cryptography from Research Papers to Products: Results from an Interview Study with Experts - Fischer, Konstantin; Trummová, Ivana; Gajland, Phillip; Acar, Yasemin; Fahl, Sascha; Sasse, M. Angela (33rd USENIX Security Symposium, USENIX Security 2024, Philadelphia, PA, USA, August 14-16, 2024)

Einleitende Überlegungen – Erneuerungen und Positionierungen der Tragödie in der Romania, 1500-1750 - Steigerwald, Jörn; Schlieper, Hendrik (Erneuerungen und Positionierungen der Tragödie in der frühmodernen Romania)

Erneuerungen und Positionierungen der Tragödie in der frühmodernen Romania

"These results must be false": A usability evaluation of constant-time analysis tools - Fourné, Marcel; Braga, Daniel De Almeida; Jancar, Jan; Sabt, Mohamed; Schwabe, Peter; Barthe, Gilles; Fouque, Pierre-Alain; Acar, Yasemin (33rd USENIX Security Symposium, USENIX Security 2024, Philadelphia, PA, USA, August 14-16, 2024)

Geschichtskulturen im digitalen Wandel?

"You have to read 50 different RFCs that contradict each other": An Interview Study on the Experiences of Implementing Cryptographic Standards - Huaman, Nicolas; Suray, Jacques; Klemmer, Jan H.; Fourné, Marcel; Amft, Sabrina; Trummová, Ivana; Acar, Yasemin; Fahl, Sascha (33rd USENIX Security Symposium, USENIX Security 2024, Philadelphia, PA, USA, August 14-16, 2024)

"But they have overlooked a few things in Afghanistan: " An Analysis of the Integration of Biometric Voter Verification in the 2019 Afghan Presidential Elections - Panahi, Kabir; Robertson, Shawn; Acar, Yasemin; Bardas, Alexandru G.; Kohno, Tadayoshi; Simko, Lucy (33rd USENIX Security Symposium, USENIX Security 2024, Philadelphia, PA, USA, August 14-16, 2024)

Security and Privacy Software Creators’ Perspectives on Unintended Consequences - Ramulu, Harshini Sri; Schmitt, Helen; Wermke, Dominik; Acar, Yasemin (33rd USENIX Security Symposium, USENIX Security 2024, Philadelphia, PA, USA, August 14-16, 2024)

Multi-objective Ranking using Bootstrap Resampling - Rook, Jeroen; Hoos, Holger H.; Trautmann, Heike (Proceedings of the Genetic and Evolutionary Computation Conference Companion, GECCO 2024, Melbourne, VIC, Australia, July 14-18, 2024)

Improving Process Mining Maturity: From Intentions to Action - Brock, Jonathan; Brennig, Katharina; Löhr, Bernd; Bartelheimer, Christian; von Enzberg, Sebastian; Dumitrescu, Roman (Business & Information Systems Engineering)

Irrläufe Herta Müllers Poetik des Eigen-Sinns - Eke, Norbert

Empirisch-kriterienorientierte Analyse des fachdidaktischen Wissens angehender Physiklehrkräfte: Welche inhaltlichen Strukturen zeigen sich über unterschiedliche Projekte hinweg? - Zeller, Jannis; Schiering, Dustin; Kulgemeyer, Christoph; Neumann, Knut; Riese, Josef; Sorge, Stefan (Unterrichtswissenschaft)
Zusammenfassung In den letzten Jahren wurde das Professionswissen (angehender) Lehrkräfte intensiv untersucht. Neben Aussagen zur inneren Struktur liegen auch Ergebnisse über den Zusammenhang zwischen Professionswissen, Performanz in prototypischen Handlungssituationen sowie Unterrichtserfolg vor. In diesen Analysen hat sich gezeigt, dass insbesondere dem fachdidaktischen Wissen eine zentrale Rolle zukommt. Es mangelt bisher jedoch an empirisch fundierten Beschreibungen von Niveaustufen des fachdidaktischen Wissens. Zwar liegen einzelne Vorschläge vor, diese sind jedoch entweder empirisch nicht fundiert oder post hoc generiert, so dass unklar ist, inwieweit die Beschreibung der Ausprägungen auch außerhalb der jeweiligen Projektkontexte anwendbar ist. Der vorliegende Artikel stellt eine projektübergreifende Analyse des fachdidaktischen Wissens mithilfe zweier Ansätze zur Bildung von Niveaustufen vor. Dazu werden Niveaumodelle mit Daten zum fachdidaktischen Wissen aus zwei Projekten ( $$N=427$$ N = 427 und $$N=779$$ N = 779 ) mithilfe des Scale-Anchoring-Verfahrens sowie eines regressionsanalytischen Ansatzes auf Basis eines Modells hierarchischer Komplexität erstellt. Das Scale-Anchoring-Verfahren liefert Niveaubeschreibungen, die sich zwar bezüglich fachlicher und fachdidaktischer Inhalte unterschieden, aber Parallelen bezüglich lernpsychologisch interpretierbarer Operatoren zeigten. Projektübergreifend deuteten die Ergebnisse daraufhin, dass sich das fachdidaktische Wissen in niedrigen Ausprägungen auf reproduktive Aspekte beschränkt, in höheren Ausprägungen aber kreative und evaluierende Elemente hinzukommen. Das Modell hierarchischer Komplexität zeigte sich nur für einen der Datensätze als geeignet, um ein Niveaumodell abzuleiten und konnte daher für projektübergreifende Analysen nicht weiter genutzt werden. Nichtsdestotrotz lieferte die projektübergreifende Analyse mithilfe des Scale-Anchoring-Verfahrens kontextunabhängige Beschreibungen von Ausprägungen des fachdidaktischen Wissens und ermöglicht so erste Schritte in Richtung eines empirisch fundierten, inhaltlich reichhaltigen Assessments, welches über eine Einordnung mittels eines Scores hinaus geht.
Keywords: Education

Evaluation of a university seminar on the use of digital media in the physics classroom - Weiler, David; Burde, Jan-Philipp; Große-Heilmann, Rike Isabel; Lachner, Andreas; Riese, Josef; Schubatzky, Thomas (Journal of Physics: Conference Series)
Abstract Fostering digital competencies is an important aspect of pre-service teacher education. However, for physics, there is a lack of systematically surveyed and evidence-based seminars that specifically take into account relevant research findings. Thus, we developed a research-based seminar on the effective use of digital media in physics classrooms and investigated its effects on pre-service teachers (PSTs) professional competencies in a mixed-methods design. Our quantitative analyses of different competence components surveyed in a pre-post-design indicate that the seminar leads to an increase in motivation to use digital media in the physics classroom. Nevertheless, no significant increase in digital-media PCK was found, which could be due to the small sample. The seminar design, however, was predominantly evaluated positively by experts and PSTs in guided interviews. Based on the results, it is planned to further refine the original seminar using a Design-Based Research approach.

Blackness in Heiner Müller’s Imaginary - Eke, Norbert (Staging Blackness: Representations of Race in German-Speaking Drama and Theater)

Renata T. Fuchs: Women Writer’s Philosophy of Love in German Ro-manticism. Dialogical Life in Letters

Heiner Müllers Natur. - Eke, Norbert (Heiner-Müller-Jahrbuch 1: Heiner Müllers Natur)

Closed-Form Expressions for Two- and Three-Colorable States - Revis, Konstantinos-Rafail; Zakaryan, Hrachya; Raissi, Zahra (arXiv:2408.09515)
Graph states are a class of multi-partite entangled quantum states, where colorability, a property rooted in their mathematical foundation, has significant implications for quantum information processing. In this study, we investigate the colorability of graph states in qudit systems to simplify their representation and enhance their practical applications. We present closed-form expressions for all two-colorable graph states. Our findings show that the closed-form expression of these states is tightly linked to the graph structure and the distribution of particles in red ($n_R$) and blue ($n_B$). Additionally, we explore a broad family of three-colorable graph states constructed from two two-colorable graph states. The closed-form expression for these states is in the form of one two-colorable state tensor product with the graph basis formed from another two-colorable state. Our approach systematically reduces the number of terms required to represent these states. Furthermore, we demonstrate that many well-known mathematical graphs, including friendship graphs, fit within our formalism. Finally, we discuss the LU/SLOCC (Local Unitary/Stochastic Local Operation and Classical Communication) equivalence between two- and three-colorable graph states. Our findings have broad implications for characterizing the LU/SLOCC equivalence of graph state classes and pave the way for future research.